Scalable measures for sustainable largescale rangelands rehabilitation - Louhaichi, Mounir (the Saudi Ministry of Environment, 2023)
ICARDA participated in the International Exhibition and Forum for Afforestation Techniques held at the Riyadh International Center, organized by the Saudi Ministry of Environment, Water and Agriculture (MoEWA), in cooperation with the National Center for the Development of Vegetation Cover and Combating Desertification (NCVCCD), May 29-31. A presentation performed by Dr. Mounir Louhaichi about sustainable largescale rangelands rehabilitation in the dry areas.